Genetic analysis of soybean aphid resistance gene in soybean K1621 - Meng, Jianye (Kansas State University, 2010)
The soybean aphid (Aphis glycines Matsumura) has been one of the major pests of soybean [Glycine max (L.) Merr.] in soybean-growing regions of North America since it was first reported in 2000. The objectives of this study were to screen for soybean aphid resistant genotypes, determine the inheritance of resistant genes, and map and validate the resistance gene in the moderate resistant genotype K1621 using simple sequence repeat (SSR) markers. A mapping population of 150 F2:3 families from the cross between K1621 and susceptible genotype KS4202 were evaluated for aphid resistance. Phenotyping was conducted on the basis of total aphid number per plant 7 days following infestation with 4 aphids. Inheritance study indicated that one major dominant gene controls soybean aphid resistance in K1621. After SSR markers for polymorphism were screened between parents, a total of 133 polymorphic markers distributed across the soybean genome were used for genotyping. One quantitative trait loci (QTL) controlling antibiotic resistance was found by using the composite interval mapping method. This QTL localized on chromosome 13 (linkage group F) between markers Sat_234 and S6814 and explained 54% of the phenotypic variation. The putative QTL was further validated by single marker analysis using an independent population derived from the cross of K1621 and Dowling. The locus for soybean aphid resistance in K1621 was named [Rag]_K1621. The markers identified and validated in this study could be useful for marker-assisted selection of [Rag]_K1621.
Keywords: Plant breeding; Crop genetics; Insect resistance; Agriculture, Agronomy (0285); Biology, Genetics (0369)